موقع الكتروني لشركة الماس - قفيشة, زينة; الحرباوي, شهد; شيوخي, مايا; ابو عمر, ميس; ابو ميزر, ندى (جامعة بوليتكنك فلسطين - تسويق الكتروني, 2023)
This abstract presents a specialized jewelry website in Palestine that focuses on selling silver jewelry. The website offers a unique feature of sending gifts to individuals, allowing users to conveniently surprise their loved ones. Additionally, the platform provides customization options, enabling customers to modify existing product designs or create their own personalized designs. This flexibility empowers users to express their creativity and create truly unique pieces. With its emphasis on quality silver jewelry, gift sending capabilities, and customization options, the website aims to cater to the diverse preferences and needs of customers in Palestine. We conducted this study with the aim of understanding the consumer behavior, attitudes, and preferences in order to design the website according to their desires and preferences, and meet the specifications they are looking for. The primary objective of the study was to determine whether our website will be well-received by people or not. Key words: silver jewelry, online jewelry store, gift delivery, customizable designs, personalized jewelry, innovation, creativity, high quality, Palestine.
no of pages 135, تسويق الكتروني 2023
Keywords: التسويق الالكتروني